Optimization of Electronic Services through Human Resource Management at the Land Office of Buleleng Regency - I Gede Harry Pramana; Ni Made Ary Widiastini; I Nengah Suarmanayasa (Budapest International Research and Critics University, 2022)
The improvement of public services to the community is one of the indicators of reform employees that is echoed by the current government. The province of Bali as a tourist attraction and destination for investors engaged in tourism should make electronic services in the land sector an important thing. Obstacles that hinder the development of E Government are human resources, infrastructure and organization. Qualitative research methods. This research was conducted at the Buleleng Regency Land Office. Researchers obtained the necessary data, namely activities to improve the quality of electronic ready data in supporting the optimization of electronic services at the Buleleng Regency Land Office. The data sources in this study were obtained from interviews, observations, documentation, and Focus Group Discussions. Mapping of human resources at the Buleleng Regency Land Office, especially the implementers of electronic data quality improvement activities, is still dominated by high school graduates whose competence is still lacking for parcel validation. The parcel validation activity requires human resources who have an educational background in the field of mapping. From ABK activities to improve the quality of electronic ready data from 2022 to 2024, the number of human resources for validation activities is still lacking and needs to be added.